Health Education on Family Knowledge and Decisions in Efforts to Prevent COVID-19 - Lindawati, Lindawati; Wasludin, Wasludin; Fadmawati, Any (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Public knowledge and awareness about COVID-19 are essential in efforts to prevent the spread of COVID-19. Respiratory tract infections that cause mild to severe symptoms range from patients recovering after one week to acute respiratory distress syndrome (ARDS), sepsis, and septic shock, as well as multi-organ failure, including acute kidney or heart failure. The family has a vital role in maintaining health by increasing knowledge, which will ultimately influence the family in making the right decisions in dealing with COVID-19. The study aimed to determine the effect of health education on COVID-19 on family knowledge and decision-making ability. The design of this study was a quasi-experimental group in 2 groups; the intervention and control groups were 25 people each. The test used is the dependent t-test in each group, which is 5%. The results of the study of knowledge in the intervention group obtained a p-value of 0.008 <0.05, and decision-making obtained a p-value of 0.000 <0.05. The results of the analysis show that there is an effect of health education on knowledge. While the knowledge variable in the control group had a p-value of 0.0952 > 0.05, The decision-making variable obtained a p-value of 0.000 < 0.05. Health education can improve health by increasing knowledge and decision-making about health behavior in dealing with COVID-19 disease.